Patronymic surnames (on the material of Ukrainian variants of Christian names) - Прадід, Юрій Федорович (Київський національний університет імені Тараса Шевченка, 2021)
The article deals with the patronymic surnames derived from Ukrainian variants of Christian names which are the most widespread among anthroponyms. The review of Ukrainian scientists’ papers dealing with studying various aspects of the anthroponymic microsystem “Patronymic surnames”, the problems of their lexicographic processing has been done. The ways of patronymic surname formation from the most widespread masculine Ukrainian variants of Christian names are investigated on large factual material. As the analysis proves, the most substantial part of surnames has been formed from the Ukrainian variants of masculine Christian names. The popularity of names both masculine does not influence the productivity of surname formation. Sometimes a less spread name may form much more surnames than a more popular one. The overwhelming majority of surnames derived both from masculine names has been formed by means of suffixation (186 or 88,6 % with 210 surnames), 77 surnames of them with the help of two suffixes (51 surnames or 27,4 % of masculine names). Non-affixal way, i.e. the case when the surname is identical with the name, gave rise to 31 surnames (24 surnames or 12,9 % from masculine names). To derive surnames from masculine names 27 suffixes are used. The most widely used suffixes to produce surnames from masculine names appeared to be suffixes -енк (-єнк) – 22 surnames correspondingly, -ук (-юк) – 20 surnames and -чук (–щук),– 18 surnames. 13 suffixes were used once to form surnames from masculine names: -ин-, -юр-, -ют-, -юш-, -ицьк-, -очк-, -н-, -ун, -аш, -ан, -ай, -ур-, -ник.

Стаття присвячена дослідженню патронімічних прізвищ, похідних від українських варіантів християнських імен, які є найпоширенішими серед антропонімів. Зроблено огляд наукових праць, у яких подано лексикографічне опрацювання антропонімів, розглянуто різні аспекти мікросистеми антропонімів “Патронімічні та матронімічні прізвища”. На великому фактичному матеріалі досліджуються способи творення патронімічних прізвищ від найпоширеніших українських варіантів християнських імен. Наголошується на тому, що основним способом творення таких прізвищ є суфіксальний спосіб. Проведений аналіз дає підстави приєднатися до думки, висловленої українськими мовознавцями раніше, і стверджувати, що більшість патронімічних прізвищ, які походять від українських варіантів християнських імен, утворені за допомогою суфіксів -ук (-юк), -чук та -енк- (-єнк-).
Патронімічні прізвища (на матеріалі українських варіантів християнських імен)
Keywords: український антропонім; мікросистема антропонімів; патронімічні прізвища; українські варіанти християнських імен; словники українських прізвищ; Ukrainian anthroponym; anthroponym microsystem; patronymic surnames; matronymic surnames; Ukrainian variants of Christian names; dictionaries of Ukrainian surnames